1997
DOI: 10.1016/s0893-133x(96)00196-0
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral and Neuroendocrine Effects of the Partial NMDA Agonist D-cycloserine in Healthy Subjects

Abstract: The effects of D-cycloserine, a partial agonist of the N-Methyl-D-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(17 citation statements)
references
References 41 publications
0
17
0
Order By: Relevance
“…However, DCS only shows an extinction effect as an adjunct, that is, when paired with behavioral training, not when given alone. DCS readily crosses the blood-brain barrier, and peak blood levels occur 1 hour after oral administration (van Berckel et al 1997). In order to pair DCS with a behavioral component to extinguish fear responses, DCS is typically administered 1 hour before therapy sessions (Norberg et al 2008).…”
Section: Dcs As An Adjunct To Psychotherapy For Ptsdmentioning
confidence: 99%
“…However, DCS only shows an extinction effect as an adjunct, that is, when paired with behavioral training, not when given alone. DCS readily crosses the blood-brain barrier, and peak blood levels occur 1 hour after oral administration (van Berckel et al 1997). In order to pair DCS with a behavioral component to extinguish fear responses, DCS is typically administered 1 hour before therapy sessions (Norberg et al 2008).…”
Section: Dcs As An Adjunct To Psychotherapy For Ptsdmentioning
confidence: 99%
“…Preclinical data suggest that cycloserine has a dose-dependent biphasic effect; at low doses (< 150 mg/d), it behaves as an agonist, whereas at higher doses (> 500 mg/d), it has an antagonist effect at the NMDA receptor. Van Berckel et al [32,33] found that at doses of 15, 50, and 150 mg/d, cycloserine was unsuccessful in eliciting neuroendocrine response as evaluated by cortisol, prolactin, and luteinizing hormone plasma levels in healthy volunteers. Conversely, 500 mg/d did increase luteinizing hormone plasma levels, but not that of cortisol and prolactin.…”
Section: Partial Agonists At the Glycine Site On The Nmda Receptor: Cmentioning
confidence: 99%
“…The medication (D-cycloserine 50 mg or placebo [PLAC]) was administered orally under supervision. Peak plasma levels of D-cycloserine are reached between 90-120 min (Van Berckel et al 1997), so participants were able to read or work before baseline measures. In addition, before the start of the study, participants completed the following questionnaires-the Spielberger State and Trait Anxiety Inventory (SSAI, STAI; Spielberger 1983), the Beck Depression Inventory (BDI; Beck et al 1988) and the Anxiety Sensitivity Index (ASI; Reiss et al 1986).…”
Section: Study Design and Proceduresmentioning
confidence: 99%
“…Each participant received one capsule 90 min before baseline measures and the study procedure. Oral D- cycloserine is readily absorbed and shows a dose-related increase in plasma concentration (Van Berckel et al 1997).…”
Section: Manikin Taskmentioning
confidence: 99%